THE INFLUENCE OF BRAND AWARENESS, PROMOTION AND PRODUCT DESIGN AGAINST HALAL LABELED COSMETIC PURCHASE DECISIONS (Jurnal Ekonomi : Journal of Economic, 2022)
The growth of cosmetics throughout 2019 grew by around 7%, this growth was based on the expansion of various types of cosmetics. Emina is one of the pioneers of beauty brands in creating halal-certified products. This study aims to determine: the effect of Brand Awareness, Promotion and Product Design on purchasing decisions and to find out how much influence Brand Awareness, Promotion and Product Design have on purchasing decisions. In this study using a quantitative approach and primary data as a source of data obtained from the results of the questionnaire. The population of this research is consumers of Emina cosmetics at the Faculty of Economics and Business, Esa Unggul University, Kebon Jeruk Jakarta. Samples were taken as many as 150 respondents using purposive sampling technique. The method of data collection is by distributing questionnaires using google form, the scale used in this study is to use a Likert scale with a scale of 1-5. This study uses multiple linear regression analysis with the influence of Brand Awareness, Promotion and Product Design as independent variables and purchasing decisions as the dependent variable. Based on the results of the research that has been done, it shows that Brand Awareness has a positive and significant effect on purchasing decisions as evidenced by the results of the t-test with a significant level of 0.000, Promotion has no effect on purchasing decisions with a significant level of 0.556, Product Design has a positive and significant effect on decisions purchases with a significant level of  0.001. Brand Awareness, Promotion and Product Design together or simultaneously affect purchasing decisions as evidenced by the F test results of 69.655 and with a significant level of 0.000.